ẢNH HƯỞNG CỦA Β-GLUCAN BỔ SUNG VÀO THỨC ĂN LÊN TĂNG TRƯỞNG VÀ TỶ LỆ SỐNG CỦA CÁ CHIM VÂY NGẮN (TRACHINOTUS OVATUS, LINNAEUS 1758) GIAI ĐOẠN GIỐNG - Nguyễn, Văn Quang; Lương, Công Trung; Đỗ, Hữu Hoàng; Cao, Văn Nguyên; Huỳnh, Minh Sang (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EFFECTS OF DIETARY ȕ-GLUCAN ON GROWTH AND SURVIVAL OF POMPANO FISH (Trachinotus ovatus, Linnaeus 1758) This study presents results of the effects of dietary ȕ-glucan (BG) on growth and survival of golden pompano, Trachinotus ovatus (mean weight 6.5 g). An experiment was conducted with four treatments with ȕ-glucan (0.0% (control), 0.05%, 0.1%, and 0.2%) supplemented in the diet. After 8 weeks of culture, the growth rate and final biomass were higher in the fish fed 0.1% BG supplemented, with significant difference among the control (P > 0.05). However, the survival rates ranked between 92 ÷ 95% with no significant difference among the treatments (P > 0.05). Coefficients of Variantion (CV) were between 24.1% in fish fed 0.05% BG to 36.9% in fish fed 0.2% BG (P < 0.05). In general, supplementation of 0.1% BG in the diet will boost growth, and final biomass of pompano fish.